From liver biopsy to non-invasive markers in evaluating fibrosis in chronic liver disease - Cătălina Diaconu; Florentina Ioniță Radu; Mariana Jinga; Petruț Nuță; Săndica Bucurică; Bogdan Macadon; Mihăiță Pătrășescu; Andrada Popescu; Vasile Balaban; Laura Voicu; Daniel O. Costache; Raluca S. Costache (Romanian Journal of Military Medicine, 2015)
Chronic liver disease is a late stage of progressive hepatic fibrosis. It consists of functional and structural disruptions in most chronic liver diseases. An accurate diagnosis allows us to establish the degree of fibrosis and the stage of the disease, the prognosis of the patient and to predict a treatment response. Despite the fact that liver biopsy is considered a gold standard, noninvasive methods for diagnosing liver fibrosis have gained more and more importance. Whether we talk about serum biomarkers or imagistic methods from transient elastography to 3-D magnetic resonance elastography, the question remains: are these useful or useless? Serum biomarkers represent blood components that can reflect liver histological changes, thus they can monitor the continuous process of fibrosis. These can be subcategorized in direct (that show extracellular matrix turnover) and indirect markers (that reflect disturbances in the hepatic function). However these markers alone are not as accurate in the staging of fibrosis, only help differentiate patients without or with low grade of fibrosis from those with significant fibrosis and cannot be considered alone in the diagnosis of liver fibrosis. Imagistic methods include: ultrasound-based transient elastography, magnetic resonance elastography (MRE), 2D-shear wave elastography, acoustic radiation impulse imaging (ARFI) and cross sectional imaging, the first being the most used. Using a combination of non-invasive tools allows us to diminish the number of patients in need of liver biopsy. However, the patient must always be informed of the advantages and disadvantages of each method and its limitations.